Is Supplemental Oxygen Needed in Cardiac Compression?—The Influence of Oxygen on Cerebral Perfusion in Severely Asphyxiated Neonates With Bradycardia or Cardiac Asystole - Solevåg, Anne Lee; Schmölzer, Georg M.; Cheung, Po-Yin (Frontiers in Pediatrics, 2019)
Background Previous studies have investigated hemodynamic recovery using 21% versus 100% oxygen during cardiopulmonary resuscitation (CPR) with chest compression (CC) in term infants. Animal studies indicate that systemic circulatory recovery is the same whether 21% or 100% oxygen is used during neonatal CPR. One of the main goals of resuscitation is to maintain cerebral oxygen delivery and prevent cerebral hypo- and hyperoxygenation. Oxygen delivery to the brain depends on cerebral hemodynamics, concentration of inhaled oxygen and blood oxygen content. The aim of this paper was to synthesize available research about cerebral oxygen delivery during CPR using different oxygen concentrations. Our research questions included how do different oxygen concentrations during CPR with CC influence cerebral perfusion and oxygen delivery, and how do cerebral hemodynamics during CC influence outcomes. Methods A search in Medline Ovid using the search terms hypoxia AND oxygen AND cerebrovascular circulation AND infant, newborn. Inclusion criteria included studies of hypoxia and resuscitation of term infants. Studies were excluded if no measures of cerebral blood flow, oxygenation, or perfusion were reported. Results The search retrieved 21 papers. None of the studies directly fulfilled our inclusion criteria. The reference lists of some of the retrieved papers provided relevant animal studies with slightly conflicting results regarding blood flow and oxygen delivery to the brain using 21% or 100% oxygen. No study in term infants was identified, but we included one study in preterm infants. Studies in asphyxiated animals indicate that 100% oxygen increases cerebral blood flow and oxygenation during and after CC with a potential increase in oxidative stress. Conclusion In asphyxia, cerebral autoregulation may be impaired. Pure oxygen administration during CC may result in cerebral hyperperfusion and increased cerebral oxygen delivery, which may be associated with oxidative stress-related damage to the brain tissue. As systemic circulatory recovery is the same whether 21% or 100% oxygen is used during neonatal CPR, it is important to investigate whether brain damage could be aggravated when 100% oxygen is used.